Anestesi Inhalasi dengan Teknik Low Fresh Gas Flow - Pratomo, Bhirowo Yudo; Kurniawaty, Juni; Kusuma, Danur Adi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Any technique that employs a fresh gas flow that is less than the alveolarventilation can be classified as low-flow anesthesia. The complexities involvedin the calculation of uptake of anesthetic agents during the closed-circuitanesthesia made this technique less popular. However, the awareness of thedangers of operating theatre pollution with trace amounts of the anestheticagents and the prohibitively high cost of the new inhalational agents, havehelped in the rediscovery of low-flow anesthesia.